THE ROLE OF REFLECTION IN CONTINUING PROFESSIONAL DEVELOPMENT IN HIGHER EDUCATION - Ug’iloy Xakimova (European Science Publishing, 2026)
Reflective practice has become a central mechanism within Continuing Professional Development (CPD) frameworks in higher education. It enables educators to evaluate teaching practices, identify growth areas, and align professional learning with institutional demands andstudent expectations. This article examines the conceptual foundations of reflection, its pedagogical value, and its challenges within CPD systems, drawing from scholarly literature to argue that reflective engagement both individualizes and democratizes academic development.